Prevalence and Determinants of Depression among Multi Drug Resistant (MDR) TB Cases Cross-Sectional Observational Study - Masood uz Zaman Babar, Manzoor Ali, Faraz Ahmed, Muhammad Hassan Shaikh, Asfahan Akhtar, Saira Abbas (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The prolonged treatment duration and socio-economic hardships are major factors that lead to the high prevalence of depression among MDR-TB patients in Pakistan. Objectives: It is aimed to establish the prevalence of depression and to identify its determinants in patients with MDR-TB in Pakistan. Methods: A cross-sectional observational study was done at several tertiary care centers and specialized TB treatment facilities in Pakistan. Consecutively, one hundred adult patients bacteriologically confirmed MDR-TB were recruited. Structured interviews and reviews of medical records were used to collect data on socio-demographic, clinical, and psychosocial variables. The Patient Health Questionnaire 9 (PHQ-9) was used to assess depression, and a score of ≥10 was considered clinically significant depression. Factors independently associated with depression were identified by performing statistical analyses, including bivariate tests and multivariable logistic regression. Results: Fifty percent of the study population suffered from depression, which was equally distributed between both genders, i.e., 60% male and 40% female. Using multivariable analysis we found that low socio-economic status (aOR: 2.1, 95% CI: 1.3–3.4, p = 0.002), inadequate social support (aOR: 1.8, 95% CI: 1.1–2.9, p = 0.015), high perceived stigma (aOR: 2.5, 95% CI: 1.5–4.1, p < 0.001), and a treatment duration of more than six months (aOR: 1.7, 95) Conclusion: The study showed that depression was very common in MDR-TB patients in Pakistan, essentially due to socio-economic challenges, lack of social support, stigma, and long duration of treatment. Our findings highlight the necessity for integrated care models that include mental health services in TB treatment programs to achieve better outcomes and quality of life for patients. Keywords: MDR-TB, Depression, Cross-Sectional Study, Socio-economic Status, Social Support, Stigma, Integrated Care